If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(n + -4) = -28 Reorder the terms: -7(-4 + n) = -28 (-4 * -7 + n * -7) = -28 (28 + -7n) = -28 Solving 28 + -7n = -28 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -7n = -28 + -28 Combine like terms: 28 + -28 = 0 0 + -7n = -28 + -28 -7n = -28 + -28 Combine like terms: -28 + -28 = -56 -7n = -56 Divide each side by '-7'. n = 8 Simplifying n = 8
| 3b-3b+b-b+b=9 | | 14w-5w+5=14 | | 6x+18=10+8x | | 0.25x+5=5+0.25x | | 15tan^3x=5tanx | | 28.00+.2x=40 | | 25y-10= | | 3(k+2)=-12 | | 5x+8-4x=0 | | 6+2(z+3)=-4(2z+6) | | 2y-3+3(3y+4)=-3(y+1) | | 1=3-c | | 2m+6=-10 | | 10/10-10/1 | | 10t+t+t-t-t=10 | | (4(y-6))/3=-2y | | -4(-m-5)-7=-11 | | 0=4p-28 | | x+10=x+90 | | 1/2x+5=1/2x-3 | | 5(p-6)=8p-21 | | -(9m+10)+2= | | 8u-8u+u-1=5 | | 12+2n=5n | | 7-5(x+8)=43 | | 8c+2b= | | 4(k+6)=56 | | -5x=3x+6 | | 9p-5p-9-2p=10 | | 6a-16=2(a-6) | | 16=6ty | | 16=6tyv |